Cell-free Circulating Mitochondrial DNA in the Serum: A Potential Non-invasive Biomarker for Ewing's Sarcoma - Yu, Man; Wan, Yan-Fang; Zou, Qing-Hua (Archives of medical research, 2012)
Altered levels of circulating cell-free mitochondrial DNA (ccf mtDNA) have been recently detected in several cancer types and have been proposed as a promising noninvasive diagnostic or prognostic biomarker. There has been no report regarding quantification of ccf mtDNA in patients with Ewing's sarcoma (EWS). Ccf mtDNA copy number in serum samples obtained from 25 patients with EWS as well as 20 age-matched individuals were detected by quantitative real-time PCR assays. A receiver operating characteristic (ROC) curve analysis was performed to evaluate the diagnostic applicability of serum ccf mtDNA as a noninvasive biomarker for discriminating between patients and healthy cohorts. The potential connection between ccf mtDNA levels and various clinicopathological factors of EWS was also determined. We found that levels of ccf mtDNA in the serum of EWS patients were significantly lower than in healthy controls. The receiver operating curve analysis demonstrated that using serum ccf mtDNA content as a molecular marker allowed distinguishing between EWS patients and healthy subjects with a sensitivity of 76.1 and a specificity of 68.4%. In addition, serum levels of ccf mtDNA were associated with the status of tumor metastasis. These results suggest that serum ccf mtDNA has the potential capacity as a novel and convenient noninvasive biomarker for molecular diagnosis of EWS. Scrutinizing quantitative changes of serum ccf mtDNA may provide valuable clues for better management of EWS patients.